Multilayer Analysis Approach in Tourism Administration in Nepal - Gautam, Sahadev (Innovative Research Journal, 2023)
The notion of tourism administration encompasses more than just the functional links between the executive, legislative, and judicial branches of government. Studies of modern tourism are collections of institutional and informal entities. As a result, both laterally and vertically, the nature of tourism administration is broad and profound. Tourism administration includes social phenomena, travel locations, travel products, and authenticity. Let’s suppose that social governance is administered through the process of tourism administration. The fundamental requirement for the tourism industry, which serves as the principal environment for tourism management, is social democracy. The essay emphasizes the interdependence between important components of tourism research in Nepal based on a meta-analysis.